2020
DOI: 10.3390/polym12122996
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of Doxorubicin-Encapsulating and TRAIL-Conjugated Poly(RGD) Proteinoid Nanocapsules for Drug Delivery Applications

Abstract: Proteinoids are non-toxic biodegradable polymers prepared by thermal step-growth polymerization of amino acids. Here, P(RGD) proteinoids and proteinoid nanocapsules (NCs) based on D-arginine, glycine, and L-aspartic acid were synthesized and characterized for targeted tumor therapy. Doxorubicin (Dox), a chemotherapeutic drug used for treatment of a wide range of cancers, known for its adverse side effects, was encapsulated during self-assembly to form Dox/P(RGD) NCs. In addition, tumor necrosis factor-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…When a single dose of the RGD-TRAIL-ELP nanoparticle was administered intraperitoneally, the COLO-205 tumor xenograft model showed nearly total tumor shrinkage. Protein electrophoresis revealed a 3.4-fold increase in the RGD-TRAIL-ELP trimer content than RGD-TRAIL [126] . P(RGD) proteinoids (where RGD is a tripeptide) comprising arginine, glycine, and aspartic acid, and proteinoid nanocapsules (NCs) were synthesized for targeted tumor therapy.…”
Section: Polymer-based Nanoparticlesmentioning
confidence: 92%
“…When a single dose of the RGD-TRAIL-ELP nanoparticle was administered intraperitoneally, the COLO-205 tumor xenograft model showed nearly total tumor shrinkage. Protein electrophoresis revealed a 3.4-fold increase in the RGD-TRAIL-ELP trimer content than RGD-TRAIL [126] . P(RGD) proteinoids (where RGD is a tripeptide) comprising arginine, glycine, and aspartic acid, and proteinoid nanocapsules (NCs) were synthesized for targeted tumor therapy.…”
Section: Polymer-based Nanoparticlesmentioning
confidence: 92%
“…Similarly, proteinoid nanocapsules have been engineered for TRAIL delivery [ 110 ]. Proteinoids are non-toxic biodegradable polymers prepared by the thermal step-growth polymerization of amino acids.…”
Section: Protein-based Systems For Nanodelivery Of Trail Pathway-targ...mentioning
confidence: 99%
“…The RGD sequence was intended to provide additional tumor targeting due to specific binding to the αvβ3 integrin, which is widely expressed on tumor cells and tumor vessels [ 112 ]. TRAIL-P(RGD) exhibited high cytotoxicity in human ovarian cancer cells while retaining the efficiency of free TRAIL [ 110 ]. Thus, proteinoid nanocapsules potentially offer increased stability for the TRAIL ligand; however, additional in vivo studies are required.…”
Section: Protein-based Systems For Nanodelivery Of Trail Pathway-targ...mentioning
confidence: 99%
“…Suitable molecules can be encapsulated within the internal core of the formed particle owing to hydrophobic residues; a marker (e.g., a fluorescent label) can be conjugated to the surface using hydrophilic residues such as amines [ 20 ]. Previous studies presented the encapsulation of various molecules for cosmetics (retinoic acid [ 21 ]), chemotherapeutics (doxorubicin and Paclitaxel [ 18 , 22 , 23 ], cannabidiol [ 24 ]), antipsychotics (Risperidone [ 25 ]) and dyes for diagnostic imaging (ICG [ 26 , 27 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Suitable molecules can be encapsulated within the internal core of the formed particle owing to hydrophobic residues; a marker (e.g., a fluorescent label) can be conjugated to the surface using hydrophilic residues such as amines [20]. Previous studies presented the encapsulation of various molecules for cosmetics (retinoic acid [21]), chemotherapeutics (doxorubicin and Paclitaxel [18,22,23], cannabidiol [24]), antipsychotics (Risperidone [25]) and dyes for diagnostic imaging (ICG [26,27]). D-arginine (R), glycine (G) and L-aspartic acid (D) were used for randomly achieving the RGD sequence within the proteinoid backbone; previous studies showed that 13% of the established proteinoids contain the RGD sequence [26,28].…”
Section: Introductionmentioning
confidence: 99%